2017
DOI: 10.12973/ejmste/77926
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Potentiality of Support Vector Machine Method in Crude Oil Price Forecasting

Abstract: Crude oil price forecasting is one of the most important topics in the field of energy research. Accordingly, numerous methods such as statistical, econometrical and intelligent approaches are applied for crude oil price forecasting. In this paper, a typical competitive learning algorithm, support vector machine (SVM), is empirically investigated to verify the feasibility and potentiality of SVM in crude oil price forecasting. For this purpose, five different prediction models, feed-forward neural networks (FN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 37 publications
0
28
0
1
Order By: Relevance
“…SVM is a type of learning algorithm proposed to improve the neural network's generalizability to achieve the global optimum solutions. SVM was first introduced for classification tasks, and it is extended for regression and time-series forecasting problems with excellent outcomes [47,109].…”
Section: Support Vector Machine (Svm)mentioning
confidence: 99%
See 1 more Smart Citation
“…SVM is a type of learning algorithm proposed to improve the neural network's generalizability to achieve the global optimum solutions. SVM was first introduced for classification tasks, and it is extended for regression and time-series forecasting problems with excellent outcomes [47,109].…”
Section: Support Vector Machine (Svm)mentioning
confidence: 99%
“…SVM has been applied in various domains for price forecasting, such as crude oil [44][45][46][47], rubber [48], gold [49], and electric [50][51][52][53], agricultural [54], and stock [55] from 2005 to 2021. SVM can avoid the over-fitting problem and model the nonlinear relationships stably, as it applied the risk minimization principle in training.…”
Section: Support Vector Machine (Svm)mentioning
confidence: 99%
“…One such technique, which has been gaining high popularity in recent years, is support vector regression (SVR). In particular, SVR and SVR-based hybrid models have been applied in many studies to forecast prices of energy commodities, including: crude oil (e.g., [13][14][15][16][17][18]) and natural gas (e.g., [19,20]). However, they have been used only by Zhang and Zhang [8] to forecast volatility of energy commodities, specifically crude oil.…”
Section: Introductionmentioning
confidence: 99%
“…To cope with the complex characteristics of crude oil prices, more and more scholars use AI models to forecast crude oil prices. The most popular AI models include artificial neural network (ANN) [12,[24][25][26][27], support vector regression (SVR) [28,29] and least squares SVR (LSSVR) [2,10,30], sparse Bayesian learning (SBL) [31,32], extreme learning machine (ELM) [23,33,34], extreme gradient boosting (XGBoost) [8], random vector functional link (RVFL) network [11], long short-term memory (LSTM) [35], and so on. Yu et al used a feed-forward neural network (FNN) to forecast each decomposed component from the raw series of crude oil prices, and then integrated the results of all components as the final forecasting result by an adaptive linear neural network (ALNN) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Barunik and Malinska found that a focused time-delay NN could achieve higher accuracy than the compared models when forecasting monthly crude oil prices [26]. Extensive research has demonstrated that the kernel-based methods, such as SVR, LSSVR and relevance vector machine, are promising for forecasting crude oil prices [2,10,[28][29][30]36]. Very recently, the LSTM, an artificial recurrent NN architecture widely used in deep learning, has been applied to forecasting crude oil prices.…”
Section: Introductionmentioning
confidence: 99%